Clonal tracking of erythropoiesis in rhesus macaques - Xing Fan; Chuanfeng Wu; Lauren L. Truitt; Diego A. Espinoza; Stephanie Sellers; Aylin Bonifacino; Yifan Zhou; Stefan F. Cordes; Allen Krouse; Mark Metzger; Robert E. Donahue; Rong Lu; et al. (Haematologica, 2020)
The classical model of hematopoietic hierarchies is being reconsidered on the basis of data from in vitro assays and single cell expression profiling. Recent experiments suggested that the erythroid lineage might differentiate directly from multipotent hematopoietic stem cells / progenitors or from a highly biased subpopulation of stem cells, rather than transiting through common myeloid progenitors or megakaryocyte-erythrocyte progenitors. We genetically barcoded autologous rhesus macaque stem and progenitor cells, allowing quantitative tracking of the in vivo clonal output of thousands of individual cells over time following transplantation. CD34+ cells were lentiviral-transduced with a high diversity barcode library, with the barcode in an expressed region of the provirus, allowing barcode retrieval from DNA or RNA, with each barcode representing an individual stem or progenitor cell clone. Barcode profiles from bone marrow CD45−CD71+ maturing nucleated red blood cells were compared with other lineages purified from the same bone marrow sample. There was very high correlation of barcode contributions between marrow nucleated red blood cells and other lineages, with the highest correlation between nucleated red blood cells and myeloid lineages, whether at earlier or later time points post transplantation, without obvious clonal contributions from highly erythroid-biased or restricted clones. A similar profile occurred even under stressors such as aging or erythropoietin stimulation. RNA barcode analysis on circulating mature red blood cells followed over long time periods demonstrated stable erythroid clonal contributions. Overall, in this nonhuman primate model with great relevance to human hematopoiesis, we documented continuous production of erythroid cells from multipotent, non-biased hematopoietic stem cell clones at steady-state or under stress.